Pergeseran Paradigma Pemidanaan Indonesia: Implikasi Normatif dan Tantangan Implementasi Keadilan Restoratif dalam KUHP Nasional 2026 - Elmarianti, Elmarianti; Aulia, Nur Insani (Al-Mizan (e-Journal), 2025)
This study discusses the paradigm shift in criminal punishment in the 2026 National Criminal Code as well as the normative implications and implementation challenges of the concept of restorative justice in the Indonesian criminal justice system ahead of its enactment in 2026.. This paradigm shift represents a fundamental transformation from a retributive approach, focused on punishing offenders toward a restorative approach that emphasizes the restoration of social relationships among offenders, victims, and the community. Normatively, the 2026 National Criminal Code introduces new provisions on conditional punishment, probationary sanctions, and case settlements through reconciliation, all of which reflect humanitarian and social justice values as embodied in Pancasila. This research employs a normative juridical method with statutory and conceptual approaches to analyze the substance of these changes and their legal implications. The findings indicate that although the restorative justice paradigm provides a new direction toward a more humanistic criminal law system, its implementation faces several challenges, including the readiness of law enforcement institutions, resistance rooted in a repressive legal culture, and the need for more operational derivative regulations. Therefore, the enforcement of the 2026 National Criminal Code serves as a crucial momentum for reforming Indonesia’s criminal law to ensure not only legal certainty but also substantive justice and social benefit for Indonesian society.